Influence of Smallholder Farmer Groups on the Application of Best Horticultural Farming Practices in Kenya - Raphael Mwiti Gikunda; David Lawver (Journal of International Agricultural and Extension Education, 2019)
This study aimed at establishing the relationship between group membership and application of best horticultural farming practices (BHFP) among the group and non-group farmers in Meru County, Kenya. A descriptive design involving a cross-sectional survey was applied to address the research objectives. The target population consisted of 4950 smallholders from horticultural group and non-group farmers. The study sample was 224 farmers chosen through stratified random sampling. Data were gathered using a researcher-developed questionnaire. Both descriptive and inferential statistics were employed in data analysis. The analysis was accomplished using the Statistical Package for Social Sciences (SPSS). The study revealed a variance in mean BHFP application scores between groups' farmers (M =76.49, SD = 4.78) and non-groups' farmers (M = 67.71, SD = 8.57). There was a positive substantial correlation between group membership and application of BHFP, which was statistically significant (rpb = .50, N = 224, p < .01). Discriminant function analysis revealed that Wilks’ lambda was significant, λ = .47, χ2 (16) = 162.63, p = <.05, R2 = .53 implying that the group means differed significantly. Farmers in groups applied BHFP more than the non-group farmers hence a clear association between group membership and BHFP application. The study recommends that farmer groups should be promoted to facilitate dissemination and application of BHFP.
Keywords: best horticultural farming practices; farmer group; smallholder farmers